Phytochemical Screening And Antibacterial Activity Of N-Hexane, Ethyl Acetate, And Ethanol Extracts Of Malacca Fruit (Phyllanthus Emblica L.) Against Escherichia Coli And Staphylococcus Aureus - Mariany Razali; Yessi Febriani; Muhammad Taufik; Eva Dasopang; Nurmala Sari; Aldy Fardiansyah; Supran Hidayat Sihotang; Rika silvany (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Phyllanthus emblica L. (Malacca fruit) is a tropical plant traditionally used for its medicinal properties. This study aimed to identify the secondary metabolite content through phytochemical screening and to evaluate the antibacterial activity of n-hexane, ethyl acetate, and ethanol extracts of Malacca fruit against Escherichia coli and Staphylococcus aureus. The simplicia was extracted using graded maceration. Phytochemical screening revealed the presence of flavonoids, terpenoids, steroids, saponins, and tannins. Antibacterial testing was performed using the agar well diffusion method at concentrations of 3.125–100 mg/mL. Results showed that all three extracts exhibited antibacterial activity against both bacteria. The ethanol extract demonstrated the highest inhibition, with zones of 23.78 mm and 21.63 mm against E. coli and S. aureus at 100 mg/mL, respectively. Inhibition zones increased with increasing extract concentration. The ethanol extract exhibited superior antibacterial activity compared to ethyl acetate and n-hexane extracts, likely due to its ability to extract a broader range of polar bioactive compounds.